SISTEM ABSENSI PERKULIAHAN BERBASIS RFID DI AKADEMI KOMUNITAS SEMEN INDONESIA GRESIK: RFID-BASED LECTURE ATTENDANCE SYSTEM AT THE ACADEMY OF SEMEN INDONESIA COMMUNITY GRESIK - Deky Islami; Mohammad Fizaluddin Sulthon; Santomi; FARIDATUN NADZIROH (Program Studi Teknologi Informasi, 2022)
The process of student attendance for an institution is a very important thing to do. The list of attendance or student attendance becomes a benchmark to determine the quality and quanlity of each student. If done manually, eating will take quite a long time and be less effective so that an absent machine is needed that can work automatically, one of which is by making an automatic attendance machine using RFID sensors. Method on RFID systems by reading chip numbers from RFID Tag cards by RFID Reader. The control system is in the form of Arduino UNO, sensor readings use RFID Mifare RC522, data is stored in the Microsoft Excel database and displayed on the PC Monitor. Tests are carried out with RFID Tag sample cards which are tested by a number of 4 cards.